Associations Between Anesthetic Variables and Functional Outcome in Dogs With Thoracolumbar Intervertebral Disk Extrusion Undergoing Decompressive Hemilaminectomy. (13th March 2017) - Fenn, J.; Laber, E.; Williams, K.; Rousse, C.A.; Early, P.J.; Mariani, C.L.; Muñana, K.R.; De Decker, S.; Volk, H.A.; Olby, N.J.
Abstract : Background: Outcome of acute experimental spinal cord injury is strongly associated with tissue perfusion and oxygenation. Cardiopulmonary depression could affect outcome in dogs undergoing general anesthesia for surgical treatment of thoracolumbar intervertebral disk extrusion (IVDE). Hypothesis/Objectives: To evaluate the effects of general anesthesia on functional outcome in dogs undergoing surgery to treat thoracolumbar IVDE. Animals: Eighty‐four client‐owned dogs with acute thoracolumbar IVDE treated by decompressive hemilaminectomy. Methods: Exploratory, retrospective observational study. Medical records were reviewed for clinical presentation and anesthetic monitoring variables, including duration of anesthesia and surgery, hypotension, bradycardia, temperature, and respiratory parameters. Multivariable regression tree analysis was performed to explore associations between anesthetic variables and functional outcome scores after 6 weeks, as well as return to ambulatory status. Results: Episodes of bradycardia (69%) and hypotension (57%) were frequent. Across all outcome measures, regression tree analysis highlighted functional grade at presentation as the primary determining factor, and among pain perception negative dogs, there was a possible association between increased duration of surgery and poorer outcome. In dogs with intact pain perception, duration of bradycardia, mean body temperature, and mean end‐tidal carbon dioxide were highlighted. Conclusions and Clinical Importance: Exploratory statistical methods can facilitate hypothesis‐generating studies to inform prospective investigations in veterinary medicine. Although the mechanism is uncertain, increased duration of surgery might be associated with poorer outcome in pain perception negative dogs with thoracolumbar IVDE.